Discovery of novel N-aryl piperazine CXCR4 antagonists - Zhao, Huanyu (Bioorg Med Chem Lett, 2015)
A novel series of CXCR4 antagonists with substituted piperazines as benzimidazole replacements is described. These compounds showed micromolar to nanomolar potency in CXCR4-mediated functional and HIV assays, namely inhibition of X4 HIV-1(IIIB) virus in MAGI-CCR5/CXCR4 cells and inhibition of SDF-1 induced calcium release in Chem-1 cells. Preliminary SAR investigations led to the identification of a series of N-aryl piperazines as the most potent compounds. Results show SAR that indicates type and position of the aromatic ring, as well as type of linker and stereochemistry are significant for activity. Profiling of several lead compounds showed that one (49b) reduced susceptibility towards CYP450 and hERG, and the best overall profile when considering both SDF-1 and HIV potencies (6–20 nM).